2015
DOI: 10.1016/j.midw.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on how Muslim women of Moroccan descent approach antenatal anomaly screening

Abstract: counsellors should have knowledge of the different Islamic beliefs about - the latest possible day for - termination and an awareness that Muslim women make their own conscious choices, also beyond Islamic rulings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In line with our recommendations, this model also suggests putting the perspective of the patient central during the start of the decision-making process, which is fundamental for patient-centered communication (SDM, choice talk) [55]. In line with the model of SDM, the counsellor should first explore to what extent expecting parents want information about possible congenital anomalies in her/their foetus and for what purpose [33,36]. Different life experiences and existential life questions may be underlying reflections in this phase.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 71%
See 2 more Smart Citations
“…In line with our recommendations, this model also suggests putting the perspective of the patient central during the start of the decision-making process, which is fundamental for patient-centered communication (SDM, choice talk) [55]. In line with the model of SDM, the counsellor should first explore to what extent expecting parents want information about possible congenital anomalies in her/their foetus and for what purpose [33,36]. Different life experiences and existential life questions may be underlying reflections in this phase.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 71%
“…How will you change as a human; will you make other choices in your life? However, such questions are seldom explicitly discussed in maternity care settings or during counselling for prenatal anomaly screening [29][30][31][32][33]. This paper argues that consideration of parents' existential life questions should underpin all counselling for prenatal anomaly screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While not specifically asked about, the stigma of living with a genetic haemoglobinopathy was spontaneously mentioned by five of the 11 participants in this group, highlighting its significance in shaping experiences of the condition, particularly among particular ethnic groups where arranged marriages and family prestige are a central part of religious, cultural and social life (Roy & Chatterjee, ; Shaw & Hurst, ; van der Wal et al, ). Indeed, Mahila described her first boyfriend's family rejecting her as the potential long‐term partner for their son on account of her “defective gene” as an “awful” experience that informed her later attitudes towards relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies have showed women's concerns in the process of undergoing AASTs from different angles (Carroll et al., 2000 ; Chiang et al., 2006 ; Gitsels‐van der Wal et al., 2015 ; Gottfreðsdóttir, 2009 ; Lewis et al., 2016 ; Potter et al., 2008 ; Reid et al., 2009 ; Tischler et al., 2011 ; Williams et al., 2005 ). For instance, a systematic review, conducted by Reid et al, examined factors affecting pregnant women's decisions regarding accepting or rejecting AASTs.…”
Section: Introductionmentioning
confidence: 99%